Myocardial crypt in an asymptomatic young athlete: How to interpret? - Neunhäuser, D.; Ermolao, A.; Corbetti, F.; Niebauer, J.; Zaccaria, M.; Gasperetti, A. (Medicine & Science in Sports & Exercise, 2015)
Myocardial crypts are extensions of blood signal penetrating the compact myocardium and are considered in literature as either a distinctive cardiac magnetic resonance (CMR) imaging marker for hypertrophic cardiomyopathy or as benign congenital malformations. What if CMR reveals a myocardial crypt in the presence of an altered ECG in an asymptomatic, enlarged young athlete`s heart? The illustrated case demonstrates that new insights in CMR can also require further diagnostic interventions, which might have deleterious consequences for the individual athlete because of the uncertain interpretation of some findings in the demanding new world of a rapidly developing diagnostic imaging technique.